Work in Tropical Forests - Lewark, Siegfried (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2022)
This book compiles in an innovative approach a synopsis of work performed in natural and plantation forests in the tropics today, its types, its abundance and the related working conditions. It covers activities of formally and informally employed as well as of self-employed and own-account small-scale forest users, in subsistence and market economy. This includes also the specifics of the substantial work by women and children. The synopsis is widely based on recently published work studies that are centered around the abilities, needs and efforts of the workers while fulfilling their tasks, resulting in performance and workload. Influencing variables from organizational, technical and managerial sides are considered as much as included in the publications. In addition to the mostly studied work in tree harvesting and processing also other activities are analyzed, in manual and motor-manual operations, like on-site conversion by pitsawing, primary transport, planting and pruning. An overview is provided for all interested in work in tropical forests, in particular students and researchers. The work studies described in detail as examples demonstrate the methodical state of the art of ergonomic research. For better understanding of the present orientation and coverage of relevant research a broad background of the development of general work science and forest work science is given. The lasting influence of Taylorism and the role of international agencies, in particular ILO and FAO, are pointed out, as well as the impact of actions by NGOs, e.g. in certification. The book is based on the broad international experience of the author in countries including Indonesia and China, over many years, and his activities in scientific networks on international level. He was teaching forest work science at university and doing related research, including the supervision of numerous theses, e.g. by Master students and PhD researchers from tropical Africa.
Part I: The Perspective of Work Science -- People and Work in Tropical Forests: An Introduction -- Work and Sustainable Forest Management -- Development of Work Science -- Part II: Sample Work Studies -- Methodology of Work Study -- Work in Plantation Forests -- Work for Industrial Forest Utilization in Natural Forests -- Work for Non-Industrial Forest Utilization in Natural Forests -- Part III: Insights from Work Science into Work in Tropical Forests -- Some Issues of Work in Tropical Forests, in a Nutshell -- Some Thoughts at the End.
Keywords: Forestry; Agriculture-Economic aspects; Industrial sociology; Forestry; Agricultural Economics; Sociology of Work